THE ROLE OF LITTLE INDUSTRY IN CAKALANG IN IMPROVING COMMUNITY INCOME AND LABOR ABSORPTION IN GIRIAN BAWAH SUB SUB DISRICT BITUNG CITY - MAYA F S SALINDEHO (Journal of International Conference Proceedings (JICP), 2019)
Government policies in the development of small industries continue to be encouraged, these are realized in various businesses, namely increasing design, technology development and quality improvement. Efforts to open access to financial resources and strengthen management which were then developed by small-scale industrial centers in the regions continued to be carried out by the government, all of which intended to encourage small businesses to continue to grow into large businesses. Various problems that are often encountered in the development of small industries, limited capital, labor problems and marketing. The purpose of this study is to determine the extent of the role of small industries in increasing business income and employment in the city of Bitung. The research method used is descriptive by collecting data from respondents in the form of structured questions to explore information related to business income and employment. The results showed that there had been an increase in income in this case the wages of workers in the Langsat joint business group engaged in small industry of skipjack smoke were 43% compared to the previous year. And furthermore there has also been an increase in employment of 17% compared to the previous year in the Joint Langsat business group which is engaged in the small industry of cakalang fumigation which is influenced by market demand and maintaining production continuity. Because in line with the increase in product demand, additional production capacity is needed which is implemented with the addition of labor